A Review of Root Pruning to Regulate Citrus Growth - Budiarto, Rahmat; Poerwanto, Roedhy; Santosa, Edi; Efendi, Darda (Journal of Tropical Crop Science, 2019)
Root is the important plant organ hiding below the soil that serves as plant supporting structure, water and nutrient supplier and assimilates storage. Root growth occurs in turn with shoot part, forming repeated cyclic pattern because of the photosynthate competition. Root growth regulation is one of the promising practices to boost the yield of fruit tree, especially citrus that is economically important and highly demanded fruit. Root pruning varied based on the scale of intensity and plant growth stage, including air root pruning, knife root pruning and modern pruning using root pruner machine mounted to a tractor. Root pruning to induce the growth of more fi brous root system and to correct root deformation at seedling stage have potentials to improve post-transplant growth. Besides, it has a potential to replace the use of chemical plant growth regulator for a more environmentally friendly practice. The pruning of root impeded the canopy growth, altered the plant water status leading to fl ower promotion. In addition, it is also a promising practice to overcome the alternate bearing on fruit tree, including citrus, through the suppressing of excessive growth and restricting the high fruit load during the ‘on year’ and allowing a better carbohydrate storage for the improvement of yield during the ‘off year’.